Preparation and Self-Repairing Properties of Urea Formaldehyde-Coated Epoxy Resin Microcapsules - Xiaoxing Yan; Yijuan Chang; Xingyu Qian (International Journal of Polymer Science)
Urea formaldehyde resin-coated epoxy resin microcapsules were prepared by two-step in situ polymerization. The effects of five factors on the yield, coverage rate, repair rate, and morphology of the microcapsules were investigated by five factors and four levels of orthogonal test. These five factors were the mass ratio of the core to the wall material (Wcore:Wwall), the mass ratio of the emulsifier to the core material (Wemulsifier:Wcore), stirring rate, deposition time, and mass ratio of the emulsifier solution to the core material (Wemulsifier solution:Wcore). The ideal technological level of microcapsule synthesis was determined. According to the results of the range and variance of yield, coverage rate, and repair rate, the comprehensive properties of microcapsules became ideal. At this time, the Wcore:Wwall was 0.8 : 1, Wemulsifier:Wcore was 1 : 100, stirring rate was 600 r/min, deposition time was 32 h, and Wemulsifier solution:Wcore was 8 : 1. When the concentration of microcapsules in the epoxy resin was 10.0%, the self-repair rate was the best and the repair rate was 114.77%. This study is expected to provide a reference value for the preparation of a microcapsule self-healing technology and lay a foundation for the subsequent development of self-healing materials.